BCLA CLEAR - Evidence-based contact lens practice. Issue 2 (April 2021) - Wolffsohn, James S.; Dumbleton, Kathy; Huntjens, Byki; Kandel, Himal; Koh, Shizuka; Kunnen, Carolina M.E.; Nagra, Manbir; Pult, Heiko; Sulley, Anna L.; Vianya-Estopa, Marta; Walsh, Karen; Wong, Stephanie; et al.
Abstract: Evidence-based contact lens practice involves finding, appraising and applying research findings as the basis for patient management decisions. These decisions should be informed by the strength of the research study designs that address the question, as well as by the experience of the practitioner and the preferences and environment of the patient. This reports reviews and summarises the published research evidence that is available to inform soft and rigid contact lens history and symptoms taking, anterior eye health examination (including the optimised use of ophthalmic dyes, grading scales, imaging techniques and lid eversion), considerations for contact lens selection (including the ocular surface measurements required to select the most appropriate lens parameter, lens modality and material selection), evaluation of lens fit, prescribing (teaching self-application and removal, adaptation, care regimen and cleaning instructions, as well as minimising risks of lens wear through encouraging compliance) and an aftercare routine.